Spinoza's Really Confused Ideas - Ruben Noorloos (Journal of Spinoza Studies)
Spinoza’s epistemology aims at the development of “adequate” and the removal of “confused” ideas. Spinoza’s theory of confusion raises many questions, however. It has often been thought that the confusion of an idea is mind-relative, such that an idea might be confused in my mind but adequate in God’s. In this paper I argue that confusion cannot be mind-relative, because an idea’s confusion is determined by what it represents and for Spinoza, ideas are individuated by their representational content. Instead, I propose that although it is possible to consider one and the same idea both adequately and confusedly, what such considerings pick up on are mind-independent features of ideas.